Moisture-dependent Engineering Properties of Chia (Salvia hispanica L.) Seeds - Guiotto, Estefania Nancy (2013)
Salvia hispanica L., whose common name is chia, is an annual herbaceous plant belonging to the Lamiaceae or Labiatae family. This botanical species, native to southern Mexico and north‐ ern Guatemala, was an important crop in pre-Columbian Mesoamerica in conjunction with corn, beans and amaranth. Chia seeds were valuated not only for food, but also for medi‐ cines and paints [1]. Its cultivation was banned by Spanish conquerors and replaced by exot‐ ic crops (wheat and barley) [2]. Nowadays, chia seeds are being reintroduced to western diets in order to improve human health. These seeds have been investigated and recommended due to their oil content with the highest proportion of α-linolenic acid (omega-3) compared to other natural source known to date [3, 4], and also because of their high levels of protein, antioxidant, dietary fiber, vita‐ mins and minerals [5, 6]. Chia seeds from Argentina exhibited 30.0 - 38.6 g oil/100 g, with 60.7 - 67.8 g/100 g of α-linolenic acid [7, 8]. Figure 1 shows the chemical composition of chia seed [9]. Chia seed is traditionally consumed in Mexico, the southwestern U.S., and South America, but it is not widely known in Europe. However, in 2009, the European Union approved chia seeds as a novel food, allowing them to comprise up to 5% of a bread product´s total matter [10]. Today, chia is mostly grown in Mexico, Bolivia, Argentina, Ecuador, Australia, and Guatemala, and it has been demonstrated that the species has great potential as a future crop plant [7, 11].Salvia hispanica fruit consist in four nutlets, similar to an indehiscent achene, which contains a single seed. These nutlets, are commercially named as seeds, and in the text, we will use this last term. The plant produces small white and dark seeds. Most of chia population that is commercially grown today contains a low percentage of white seeds. Their shapes are oval and in general, the white seeds are somewhat larger than the black ones. Ixtaina et al. [12], reported length, width and thickness value of 2.11, 1.32 and 0.81 mm for dark seeds and 2.15, 1.40 and 0.83 mm for white seeds, respectively. Chia seeds are shown in Figure 2. Figure 2. Photographs of dark and white chia seeds (13x) The knowledge of engineering properties constitutes important and essential data for the design of machines, storage structures, and processes. The value of this basic information is not only important to engineers but also to food scientists, processors, and other scientists who may exploit these properties and find new uses.Engineering seed properties and their dependence on moisture content are necessary in the design of equipment for transporting, storage and/or processing. The knowledge of the mor‐ phology and size distribution of chia seeds is essential for the adequate design of the equip‐ ment for cleaning, grading and separation. Gravimetric properties are useful for the design of equipment related to aeration, drying, storage and transport. Bulk density determines the capacity of storage and transport systems while true density is useful for separation equip‐ ment; porosity of the mass of seeds determines the resistance to airflow during the aeration and drying of seeds. The frictional properties, such as the angle of repose and the static coef‐ ficient of friction, are important for the design of grain bins and other storage structures whose operation is influenced by the compressibility and flow behaviour of materials. Sev‐ eral researchers investigated the moisture dependence of engineering properties of seed or grain and reported different behaviour of these properties as a function moisture content. The aim of this work was to evaluate the engineering properties of dark chia seed as a func‐ tion of the moisture content and to compare their behavior with that of other grains.